ANALISIS PELAYANAN RUAS JALAN BUNG TOMO DI KOTA SAMARINDA - PRATAMA, ZAKARIA (KURVA S JURNAL MAHASISWA, 2018)
Bung Tomo Street In Samarinda is a collector road that serves to serve collection or dividing transport with the characteristics of moderate distance travel, moderate average speed and limited number of access roads. This Bung Tomo road in Samarinda belongs to the class III C road category. As the economy develops and he level of prosperity of the population increases, the level of travel will increase, due to the need for transportation from the community, where people will always look for a faster, safer way and smooth. The increase in population and the amount of urbanization to urban areas will lead to a level of movement and density, so the need for transportation also increases. On This Basis, the research was carried out on how thr performance of vehicles passing through the Bung Tomo road in Samarinda to the development of current flows from time to time. The analysis of the Bung Tomo Road Section uses the Indonesian Road Capacity Manual (MKJI’1997), which is described based on form UR-1 in the form of general and road geometric conditions, UR-2 in the form of advanced input data namely Traffic Flow and Composition and Obstacles In addition, UR-3 consists of analysis of the speed of free flow of light vechicles capacity and speed of light vehicles. In The Analysis Of Bung Tomo Road Section Service Analysis in Kota Samarinda , a peak hour survey was conducted for 1 week, the survey was conducted at 07.00-08.00, 13.00-14.00, 17.00-18.00. after calculating the available data, he peak hour segment occurred on Wednesday, in traffic volume of 2181.89 pcu / hour, degree of saturation of 0.14, speed 33km / h, travel time of 0.0242 hours and the level of service is at level C. which means the current zone is stable, the driver is limited to choosing speed. Then at the Ring Road instersection the 2 hour peak occurred on Thursday, at traffic volume of 2181.89 pcu / hour, degree of saturation of 0.14, speed of 33 km / h, travel time of 0.0242 hours and level of service at level C. which means the current zone is stable, the driver has the freedom to choose speed.